Transverse Gas Jet Injection—Effect of Density Ratio - Balaji S.; Kumar D.; Parasuram I.; Sinha A. (My University, 2025)
Transverse jet injection or jet in crossflow is the focus of the present study. Available literature is focused on iso-density jets; and jets with density different from crossflow are usually overlooked. However, in most practical examples, the jet and crossflow have different densities. This study attempts to investigate the effect of density ratio on jet penetration and trajectory. Gas jets with different densities are numerically simulated and their trajectories are compared. It is observed that the jet penetration is strongly dependent on the density ratio. A trajectory equation is formulated using multi-variable regression. This equation is found to match well with the available data. © 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.